Exogenous melatonin protects preimplantation embryo development from decabromodiphenyl ethane-induced circadian rhythm disorder and endogenous melatonin reduction. (1st January 2022) - Shi, Feifei; Qiu, Jinyu; Zhang, Shaozhi; Zhao, Xin; Feng, Daofu; Feng, Xizeng
Abstract: Decabromodiphenyl ethane (DBDPE) is a novel flame retardant that is widely used in plastics, electronic products, building materials and textiles. Our previous studies have revealed the oocyte toxicity of DBDPE, but the effect of DBDPE on preimplantation embryo development has not been reported. Here, we investigated whether and how DBDPE exposure affects preimplantation embryo development. Adult female mice were orally exposed to DBDPE (0, 5, 50, 500 μg/kg bw/day) for 14 days. First, we found that after DBDPE exposure, mice showed obvious circadian rhythm disorder. Moreover, the development of preimplantation embryos was inhibited in DBDPE-exposed mice after pregnancy. Then, we further explored and revealed that DBDPE exposure reduced the endogenous melatonin (MLT) level during pregnancy, thereby inhibiting the development of preimplantation embryos. Furthermore, we discovered that exogenous MLT supplementation (15 mg/kg bw/day) rescued the inhibition of preimplantation embryo development induced by DBDPE, and a mechanistic study demonstrated that exogenous MLT inhibited the overexpression of ROS and DNA methylation at the 5-position of cytosine (5-mC) in DBDPE-exposed preimplantation embryos. Simultaneously, MLT ameliorated the DBDPE-induced mitochondrial dysfunction by increasing the mitochondrial membrane potential (MMP), ATP, and Trp1 expression. Additionally, MLT restored DBDPE-induced changes in zona pellucida (ZP) hardness and trophectoderm (TE) cortical tension. Finally, the protective effect of MLT on embryos ameliorated the adverse reproductive outcomes (dead fetus, fetus with abnormal liver, fetal weight loss) induced by DBDPE. Collectively, DBDPE induced preimplantation embryo damage leading to adverse reproductive outcomes, and MLT has emerged as a potential tool to rescue adverse reproductive outcomes induced by DBDPE. Graphical abstract: Image 1 Highlights: Decabromodiphenyl ethane (DBDPE) caused circadian rhythm disorder in mice. DBDPE exposure blocked embryo development. DBDPE reduced endogenous melatonin levels. Melatonin restored DBDPE-induced developmental inhibition. Melatonin ameliorated the DBDPE-induced adverse reproductive outcomes.